Construction of the Megaterminal Multimodal Transport for compliance Plan 2008-2021 Region Lima - Sarango Cruz, Oscar Alfredo (2019)
The objective of the study was to determine the influence of the construction of the Bahía Salinas Multimodal Mega Terminal, as a solution alternative for the implementation of the 2008-2021 Concerted Development Plan of the Lima Region and to overcome the insufficient level of investment. Also, considering that its implementation will be via Public Private Partnerships (APP); the way in which the south interoceanic was adjudicated was explained, given that its implementation meant cost overruns and acts of corruption, to the detriment of the State. Facts to consider, so as not to make the same mistakes; given the new private investment promotion system, “Invierte. pe”. It's a research of type explanatory, not experimental; The proponents of the project were interviewed and the interrogations of the Investigative Commissions of the Congress of the Republic, to the officials who participated in the process of awarding public works, in particular, of the South Interoceanic Highway. Finally, the conclusions and recommendations of the investigation demonstrate the relevance of the project, as well as the perception that the regional authorities have, that its implementation will increase the level of investments and will allow the improvement of the physical infrastructure and the quality of the services.